Missed opportunities for immunisation in health facilities in the Western Cape metro - Jacob, Nisha Anne Sunny (Department of Public Health and Family Medicine, 2016)
Background: Childhood immunisations are a cost effective public health intervention for prevention of infectious diseases. Immunisation coverage, however, is still sub-optimal which may result in disease outbreaks. Immunisation at every contact with a health facility is a strategy developed by the World Health Organization (WHO) in order to improve immunisation coverage. Objectives: The aim of this study was to estimate the prevalence of missed opportunities for immunisation at different levels of healthcare in the Western Cape and assess factors associated with missed opportunities. Methods: The study included a health-facility based cross-sectional exit survey of caregivers with children up to 5 years of age, followed by a qualitative exploration of staff attitudes towards immunisation. Results: The prevalence of missed opportunities for immunisation was 4.6%; 81.3% of caregivers brought Road-To-Health- Booklets (RTHB's) to consultations. Overall, 56.0% of health workers requested to see the RTHB's during consultations. Children attending primary level facilities were significantly more likely to have their RTHB's requested than children attending a tertiary level facility. Lack of training, resources and heavy workloads were the main challenges reported at secondary/tertiary level facilities.